Data distribution strategy based on the X-RDP array codes - Wu-nan WAN; Wang SUO; Yun CHEN; Tuo WANG (Tongxin xuebao)
A data distribution strategy based on the X-RDP code was presented for correcting triple storage failures, which is an extension of the double-erasure-correcting RDP code. A theoretical proof that the X-RDP code is an MDS code was given by using algebraic definition. The encoding and decoding procedures were described by geometrical line graphs, which were easily implemented by soft hardware. The theoretical analysis shows that the comprehensive proper-ties of the X-RDP codeis better than other popular MDS codes in encoding and decoding efficiency, small writes and bal-ance performance, thus the X-RDP code is practically meaningful for storage systems.